Genotipificación de la region 3 UTR del gen Nramp1, en ganado Holstein y en criollo Hartón del Valle (2006)
ABSTRACT: Summary In studies of natural resistance or susceptibility to different intracellular pathogens the Nramp1 gene has been described as controlling this characteristic in mouse and in the humans. In this project we genotyped 151 Harton of the Valle bovine individuals and 128 Holstein, for a microsatellite of the 3’ untranslated region of Nramp1 gene, in position 1745-1955 and found that the most frequency size of microsatellite were 207 and 211 bp. The sequencing results indicate that there is polymorphim in the number of GT repetitions and (GT)12 and (GT)11 were present as reported previously, as well as (GT)14 y (GT)10.